2005
DOI: 10.1128/jvi.79.8.4896-4907.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD4+T-Cell Responses to Epstein-Barr Virus (EBV) Latent-Cycle Antigens and the Recognition of EBV-Transformed Lymphoblastoid Cell Lines

Abstract: There is considerable interest in the potential of Epstein-Barr virus (EBV) latent antigen-specific CD4؉ T cells to act as direct effectors controlling EBV-induced B lymphoproliferations. Such activity would require direct CD4؉ T-cell recognition of latently infected cells through epitopes derived from endogenously expressed viral proteins and presented on the target cell surface in association with HLA class II molecules. It is therefore important to know how often these conditions are met. Here we provide CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
163
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(173 citation statements)
references
References 33 publications
10
163
0
Order By: Relevance
“…Focusing on three such epitopes, we found that two (SNP and VYG), were detectably displayed on the surface of unmanipulated LCL cells but at very low levels, whereas a third (PQC) was never detectable; indeed, this held true even when EBNA1 expression was increased by >100-fold from a dox-regulated vector. Such findings reinforce a theme seen in earlier work where EBNA1 epitope display on the LCL surface was generally poor, with several epitopes never detected, compared to epitopes from other endogenously expressed EBV proteins, EBNA2, -3A, and -3C (10,12,13).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Focusing on three such epitopes, we found that two (SNP and VYG), were detectably displayed on the surface of unmanipulated LCL cells but at very low levels, whereas a third (PQC) was never detectable; indeed, this held true even when EBNA1 expression was increased by >100-fold from a dox-regulated vector. Such findings reinforce a theme seen in earlier work where EBNA1 epitope display on the LCL surface was generally poor, with several epitopes never detected, compared to epitopes from other endogenously expressed EBV proteins, EBNA2, -3A, and -3C (10,12,13).…”
Section: Resultssupporting
confidence: 78%
“…CD4 + T cells against all three epitopes showed strong recognition of HLAmatched, peptide-loaded targets. However, as seen in earlier work (13), assays on unmanipulated LCLs revealed clear interepitope differences. Clones against the PQC epitope consistently failed to recognize such targets, whereas clones against the SNP and VYG epitopes showed low level recognition (typically 1-2% of that seen with peptide loading) that titrated with T cell input and was clearly specific, being restricted to LCLs with the appropriate HLA-DR restricting allele (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…That study also provided some evidence that CD4 + T-cell recognition is also regulated later, as the structural protein gp350 could be detected by CD4 + T cells in cells 15 d post infection but only when miRNAs were absent (35). The mechanisms of regulation we identified in that context-that is, regulation of MHC II, lysosomal enzymes, and IL-12-are likely relevant in latency as well and may explain why EBNA-specific CD4 + T cells are generally impaired in recognizing LCLs (46). The present study focused on established latency, but because we observed a strong miRNA regulation of EBNA1 recognition by CD8 + T cells already on days 1, 2, and 3 after infection, the hypothesis that EBV miRNAs generally suppress CD8 + T-cell recognition already in the first days of infection during prelatency (13,22,47) deserves closer investigation in the future.…”
Section: Discussionmentioning
confidence: 89%